Behavioural differences in consumption of children and adults: A field study - Farreras González, Verónica Inés (2012)
In general, children and adultsí consumption behaviour is analysed within the household decision-making process. This paper, however, explores children and adultsí consumption behaviour contemplating children and adults as two separated and independent economic agents. By using a Öeld study that involves observation in the Spainís Barcelona zoo, we show that children have some form of preferences that di§ers from that of the adults, leading to di§erent consumption behaviour between adults and children. This Önding reinforces the idea that children play an important role as economic decision makers and consumers.